"Save the Pacific Northwest tree octopus": a hoax revisited. Or: How vulnerable are school children to fake news?. Issue 9 (30th October 2018) - Loos, Eugène; Ivan, Loredana; Leu, Donald
Abstract : Purpose: This paper aims to propose a new literacies approach to get insight into young people's capability to detect fake news. Design/methodology/approach: This study is a replication of a US empirical study in The Netherlands to examine whether schoolchildren were able to identify the spoof website "Save The Pacific Northwest Tree Octopus" as fake. Findings: In The Netherlands, only 2 out of 27 school children (7 per cent) recognized the website as being a hoax; results that are worse, even, than those of the 2007 US study, where the website was recognized as being unreliable by slightly more than 6 out of 53 school children (11 per cent). Research limitations/implications: A similar but large-scale quantitative empirical study should be conducted in several countries to see if the trends in the US and The Netherlands are indeed significant. Practical implications: It is important to start teaching children at an early age how to critically evaluate online information. Social implications: The perceived reliability of digital information is a hot issue, given the frequency with which fake news is circulated. Being able to critically evaluate digital information will help to have access to trustworthy information. Originality/value: Instead of using technological fact checking by Google, Facebook and Twitter, this paper suggests the adoption of a new literacies approach, focusing on young people's capability to detect fake news.